TMAO-Activated Hepatocyte-Derived Exosomes Impair Angiogenesis via Repressing CXCR4 - Liu, Xiang; Shao, Yijia; Tu, Jiazichao; Sun, Jiapan; Dong, Bing; Wang, Zhichao; Zhou, Jianrong; Chen, Long; Tao, Jun; Chen, Jimei (Frontiers in Cell and Developmental Biology, 2022)
Objective: Trimethylamine-N-Oxide (TMAO) was found to play crucial roles in vascular endothelial function. However, the exact molecular mechanisms are not yet entirely clear. Recently, we found that exosomes (Exos) isolated from TMAO-treated hepatocytes (TMAO-Exos) contained a distinct profile of miRNAs compared to those from the TMAO-free group (Control-Exos). Furthermore, TMAO-Exos could notably promote inflammation, damage vascular endothelial cells (VECs) and impair endothelium-dependent vasodilation. This study aimed to further evaluate the effects of TMAO-Exos on VECs and explore the underlying mechanisms. Methods: Exos were isolated from the hepatocyte culture supernatant with or without TMAO, using differential centrifugation. Then VECs were treated with these Exos for 48 h and subjected to RNA-sequencing for detecting the changes of alternative polyadenylation (APA) and mRNA. After validation by qPCR and western blotting, the recombinant viruses were used to mediate the overexpression of C-X-C motif chemokine receptor 4 (CXCR4). The in vitro VECs function was evaluated by cell migration and tube formation, and in vivo angiogenesis was investigated in hind-limb ischemia models. Results: Exos released from hepatocytes were differentially regulated by TMAO, both could be taken up by VECs, and furthermore, TMAO-Exos significantly reduced cell migration and tube formation in vitro, and impaired perfusion recovery and angiogenesis after hindlimb ischemia, by down-regulating the CXCR4 expression. However, TMAO-Exos failed to regulate the splicing events, at least in this experimental setting, which suggested that TMAO-Exos may affect CXCR4 expression via an APA-independent manner. Conclusions: Our findings revealed a novel indirect mechanism by which TMAO impaired endothelial function through stimulating hepatocytes to produce Exos that possessed distinct activity. The crosstalk between liver and vascular endothelial mediated by these Exos may offer a new target for restraining the harmful effects induced by TMAO.